Effectiveness of a health education intervention on utilization of maternity benefit schemes among tribal pregnant women: a quasi-experimental study - Anju Damu Ade; Visweswara Rao Guthi; Nagaraj Kondagunta; Chandrasekhar Vallepalli; D. S. Sujith Kumar; Ravi Sankar Deekala; T. V. D. Prathyusha (International Journal Of Community Medicine And Public Health, 2026)
Background: Recognizing the pivotal role mothers play in society, government in India, have implemented various schemes and initiatives aimed at supporting maternal health and well-being. Main objective was to evaluate effectiveness of health promotion intervention through community mobilization with women groups facilitated by ASHAs and ANMs on utilization maternity benefit schemes of the government and to find out the reasons for non-utilization of maternity benefit schemes of the government. Methods: This was a quasi-experimental study design undertaken to evaluate educational intervention package among schedule tribe pregnant women to improve utilization of maternity benefit schemes in Chittoor District of Andhra Pradesh state in south India. A baseline household survey with the help of a semi structured questionnaire was conducted in both intervention group (n=109) and control group (n=119). An educational intervention was implemented. Data was analysed using SPSS Version 26.0. Results: In the end-line survey, there was improvement in utilization of government maternity benefit schemes among tribal pregnant women with respect to programmes/schemes like Ayushman Bharat, JSY, JSSK, PMSMA, Anemia Mukt Bharat, 102 (Thallibidda Express) and the various reasons reported by them for non-utilization of services were lack of awareness, no bank account, no Aadhar cards etc. Conclusions: To improve awareness and utilization of health services provided under various maternity benefit schemes, health education should be imparted on regular basis to mothers. For this ASHA, ANM and medical officers should be motivated to educate as they work closely with the community.